Gentrification, transnational gentrification and touristification in Seville, Spain - Jover, Jaime (2020)
Increased international tourism in large European cities has been a growing social and political issue over the last few years. As the number of urban tourists has rapidly grown, studies have often focused on its socio-spatial consequences, commonly referred to as touristification, and have linked this to gentrification. This connection makes sense within the framework of planetary gentrification theories because the social injustices it generates in cities have a global pattern. However, gentrification is a complex process that must be analytically differentiated from tourism strategies and their effects. Whereas gentrification means a lower income population replaced by one of a higher status, touristification consists of an increase in tourist activity that generally implies the loss of residents. Strategies to appropriate and marketise culture to sustain tourismled economies can also shape more attractive places for foreign wealthy newcomers, whose arrival has been theorised as transnational gentrification. Discussions on the relationship between gentrification, transnational gentrification and touristification are essential, especially regarding how they work in transforming an urban area’s social fabric, for which Seville, Spain’s fourth largest city with an economy specialised in cultural tourism, provides a starting point. The focus is set on the processes’ timelines and similar patterns, which are tested on three consecutive scales of analysis: the city, the historic district and the Alameda neighbourhood. Through the examination of these transformations, the article concludes that transnational gentrification and touristification are new urban strategies and practices to revalorise real estate and appropriate urban surplus in unique urban areas.